Correct electrostatic treatment of noncovalent interactions: the importance of polarization - Clark, Timothy; Politzer, Peter; Murray, Jane S. (Wiley Interdisciplinary Reviews: Computational Molecular Science, 2015)
The Hellmann-Feynman theorem assures us that the forces felt by the nuclei in a molecule or complex are purely classically electrostatic. Nevertheless, it is often claimed (incorrectly) that electrostatic considerations are not sufficient to explain noncovalent interactions. Such assertions arise largely from neglecting the polarization that is inherently part of the electrostatic interaction, and must be taken into account. Accordingly, we now outline the requirements for a correct electrostatic treatment and discuss the difference between physical observables and quantities that arise from mathematical models. Polarization and donor-acceptor charge transfer are shown to be equivalent for weak interactions. However, polarization is a physical observable while charge transfer, in this context, is mathematical modelling. We also discuss some popular schemes for analyzing noncovalent interactions. (C) 2014 John Wiley & Sons, Ltd.